Clinical characteristics, risk factors, and outcomes after adjuvant radiotherapy for patients with thymoma in the United States: analysis of the Surveillance, Epidemiology, and End Results (SEER) Registry (1988–2013). (2nd April 2018) - Mou, Haibo; Liao, Qin; Hou, Xuehua; Chen, Te; Zhu, Yuping
Abstract: Purpose: The surgery with adjuvant radiation for the treatment of thymoma is still debated. The aim of this study was to examine the efficacy of postoperative radiotherapy (PORT) in a population-based registry of patients with thymoma. Materials and methods: We conducted a retrospective analysis of the Surveillance, Epidemiology, and End Results database to compare the outcomes of patients with thymoma who received surgery with or without PORT. Results: Among the 2234 patients of this study, the surgery with PORT group had a longer mean overall survival (OS) and cancer-specific survival (CSS) than did the surgery without PORT group (OS: 172.3 vs. 155.3 months, p  = .005; CSS: 247.3 vs. 241.8 months, p  = .04). PORT significantly improved OS and CSS of patients with stage III/IV disease, but decreased CSS for those with stage I/IIA disease. Although the surgery with PORT group had a higher rate of secondary cancers, the between-group difference in the disease-free interval was not significant. Conclusions: PORT provides a significant benefit for patients with thymoma, particularly those with advanced disease. However, it also increases the risk of a second malignancy. We suggest that treatment guidelines should adopt a more positive stance on the use of PORT.